Trends in The Study of Administration - Ortiz Ayala, Ricardo; Valencia Perez, Hector Fernando; Espino Rico, Gustavo (Archives of Business Research, 2024)
Knowledge and information are two very important components in society, to the extent that the term "knowledge societies" has been coined (UNESCO 2021). As part of the processes in organizations, knowledge leads to improvements in their development and productivity (Muñoz and Riverola, cited by Flores 2005); therefore, they must adapt to the demands of a competitive and changing international world. Year after year, administration, specifically those areas that comprise it, results in different themes being developed considering administrative practice worldwide. Considering this, an essay is carried out as a result of exploring the research trends in administration with the goal of conducting a comparative analysis between the current research trends in the field of administration published in journals and the holographic cultural model proposed by Dr. Antonio Castañeda Ríos, and in the process, verifying if the holographic cultural model is still relevant or alternatively describing the trends that are not included in the aforementioned model. Journals that compile research from all over the world have been consulted to identify predominant themes, and it was found that current trends in the field of administration agree with the general lines of research set out in the Holographic Cultural Model. Regarding the particularities found, such themes arise as a result of the logical evolution of time and change.